Bulk nanogranular composite of magnetic metal and insulating oxide matrix. (1st March 2016) - Suetsuna, T.; Suenaga, S.; Harada, K.
Abstract: A novel bulk nanogranular composite of millimeter thickness which was composed of magnetic nanogranular flakes and insulating matrix was fabricated. In the flakes, magnetic metallic nanoparticles were highly dispersed in the oxide matrix, and the nanogranular structure of metal/oxide produced low eddy-current loss at high frequency. Furthermore, each of the nanoparticles interacted with the neighboring particles through magnetic exchange coupling in the flakes, and the composite exhibited good soft magnetism of low coercivity and high permeability. The maximum saturation magnetization of the composite was 0.94 T, which was much higher than that of conventional NiZn ferrites. Graphical abstract: